Healing country together: A seagrass restoration case study from Gathaagudu (Shark Bay) - Elizabeth A. Sinclair; John Statton; Rachel Austin; Martin F. Breed; Richard Cross; Alex Dodd; Amrit Kendrick; Siegfried L. Krauss; Bianca McNeair; Nykita McNeair; Sean McNeair; Marika Oakley; et al. (Ocean & Coastal Management, 2024)

Economic values for ecosystem services: A global synthesis and way forward - L.M. Brander; R. de Groot; J.P. Schägner; V. Guisado-Goñi; V. van 't Hoff; S. Solomonides; A. McVittie; F. Eppink; M. Sposato; L. Do; A. Ghermandi; M. Sinclair; et al. (Ecosystem Services, 2024)

Measuring Food Security among American Indian and Alaska Native Adults: Validity Evidence Supports the Use of the US Department of Agriculture Module - Cassandra J. Nguyen; Brian F. French; Tara L. Maudrie; Gary L. Ferguson; Valarie Blue Bird Jernigan; Ka`imi A. Sinclair (Journal of the Academy of Nutrition and Dietetics, 2023)

Polanyi adsorption potential theory for estimating PFAS treatment with granular activated carbon - Jonathan B. Burkhardt; Adam Cadwallader; Jonathan G. Pressman; Matthew L. Magnuson; Antony J. Williams; Gabriel Sinclair; Thomas F. Speth (Journal of Water Process Engineering, 2023)

Regenerated trees in farmers’ fields increase soil carbon across the Sahel - J. Bayala; J. Sanou; H. R. Bazié; R. Coe; A. Kalinganire; F. L. Sinclair (Agroforestry Systems, 2020)

Enhancing maize productivity in agroforestry systems through managing competition: lessons from smallholders’ farms, Rift valley, Kenya - J. Nyaga; C. W. Muthuri; E. Barrios; I. Öborn; F. L. Sinclair (Agroforestry Systems, 2019)

A review of contemporary patterns of endemism for shallow water reef fauna in the Red Sea - Joseph D. DiBattista; May B. Roberts; Jessica Bouwmeester; Brian W. Bowen; Darren J. Coker; Diego F. Lozano‐Cortés; J. Howard Choat; Michelle R. Gaither; Jean‐Paul A. Hobbs; Maha T. Khalil; Marc Kochzius; Robert F. Myers; et al. (Journal of Biogeography, 2016)
Aim The Red Sea is characterised by a unique fauna and historical periods of desiccation, hypersalinity and intermittent isolation. The origin and contemporary composition of reef‐associated taxa in this region can illuminate biogeographical principles about vicariance and the establishment (or local extirpation) of existing species. Here we aim to: (1) outline the distribution of shallow water fauna between the Red Sea and adjacent regions, (2) explore mechanisms for maintaining these distributions and (3) propose hypotheses to test these mechanisms. Location Red Sea, Gulf of Aden, Arabian Sea, Arabian Gulf and Indian Ocean. Methods Updated checklists for scleractinian corals, fishes and non‐coral invertebrates were used to determine species richness in the Red Sea and the rest of the Arabian Peninsula and assess levels of endemism. Fine‐scale diversity and abundance of reef fishes within the Red Sea were explored using ecological survey data. Results Within the Red Sea, we recorded 346 zooxanthellate and azooxanthellate scleractinian coral species of which 19 are endemic (5.5%). Currently 635 species of polychaetes, 211 echinoderms and 79 ascidians have been documented, with endemism rates of 12.6%, 8.1% and 16.5% respectively. A preliminary compilation of 231 species of crustaceans and 137 species of molluscs include 10.0% and 6.6% endemism respectively. We documented 1071 shallow fish species, with 12.9% endemic in the entire Red Sea and 14.1% endemic in the Red Sea and Gulf of Aden. Based on ecological survey data of endemic fishes, there were no major changes in species richness or abundance across 1100 km of Saudi Arabian coastline. Main conclusions The Red Sea biota appears resilient to major environmental fluctuations and is characterized by high rates of endemism with variable degrees of incursion into the Gulf of Aden. The nearby Omani and Arabian Gulfs also have variable environments and high levels of endemism, but these are not consistently distinct across taxa. The presence of physical barriers does not appear to explain species distributions, which are more likely determined by ecological plasticity and genetic diversity.

Diversity enhances carbon storage in tropical forests - L. Poorter; M. T. van der Sande; J. Thompson; E. J. M. M. Arets; A. Alarcón; J. Álvarez‐Sánchez; N. Ascarrunz; P. Balvanera; G. Barajas‐Guzmán; A. Boit; F. Bongers; F. A. Carvalho; et al. (Global Ecology and Biogeography, 2015)
Aim Tropical forests store 25% of global carbon and harbour 96% of the world's tree species, but it is not clear whether this high biodiversity matters for carbon storage. Few studies have teased apart the relative importance of forest attributes and environmental drivers for ecosystem functioning, and no such study exists for the tropics. Location Neotropics. Methods We relate aboveground biomass ( AGB ) to forest attributes (diversity and structure) and environmental drivers (annual rainfall and soil fertility) using data from 144,000 trees, 2050 forest plots and 59 forest sites. The sites span the complete latitudinal and climatic gradients in the lowland Neotropics, with rainfall ranging from 750 to 4350 mm year −1 . Relationships were analysed within forest sites at scales of 0.1 and 1 ha and across forest sites along large‐scale environmental gradients. We used a structural equation model to test the hypothesis that species richness, forest structural attributes and environmental drivers have independent, positive effects on AGB . Results Across sites, AGB was most strongly driven by rainfall, followed by average tree stem diameter and rarefied species richness, which all had positive effects on AGB . Our indicator of soil fertility (cation exchange capacity) had a negligible effect on AGB , perhaps because we used a global soil database. Taxonomic forest attributes (i.e. species richness, rarefied richness and Shannon diversity) had the strongest relationships with AGB at small spatial scales, where an additional species can still make a difference in terms of niche complementarity, while structural forest attributes (i.e. tree density and tree size) had strong relationships with AGB at all spatial scales. Main conclusions Biodiversity has an independent, positive effect on AGB and ecosystem functioning, not only in relatively simple temperate systems but also in structurally complex hyperdiverse tropical forests. Biodiversity conservation should therefore be a key component of the UN Reducing Emissions from Deforestation and Degradation strateg y.

Farmers in Côte d’Ivoire value integrating tree diversity in cocoa for the provision of ecosystem services - E. Smith Dumont; G. M. Gnahoua; L. Ohouo; F. L. Sinclair; P. Vaast (Agroforestry Systems, 2014)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Planetary Stewardship in an Urbanizing World: Beyond City Limits - Sybil P. Seitzinger; Uno Svedin; Carole L. Crumley; Will Steffen; Saiful Arif Abdullah; Christine Alfsen; Wendy J. Broadgate; Frank Biermann; Ninad R. Bondre; John A. Dearing; Lisa Deutsch; Shobhakar Dhakal; et al. (Ambio, 2012)

A global assessment using PCR techniques of mycorrhizal fungal populations colonising Tithonia diversifolia - R. A. Sharrock; F. L. Sinclair; C. Gliddon; I. M. Rao; E. Barrios; P. J. Mustonen; P. Smithson; D. L. Jones; D. L. Godbold (Mycorrhiza, 2004)

On-farm evaluation of the establishment of clonal rubber in multistrata agroforests in Jambi, Indonesia - S. E. Williams; M. van Noordwijk; E. Penot; J. R. Healey; F. L. Sinclair; G. Wibawa (Agroforestry Systems, 2001)

Productivity and profitability of multistrata organic versus conventional coffee farms in Costa Rica - A. E. Lyngbæk; R.G. Muschler; F. L. sinclair (Agroforestry Systems, 2001)

Characterization of multistrata silvopastoral systems on seasonally dry pastures in the Caribbean Region of Colombia - Y. S. Cajas-Giron; F. L. Sinclair (Agroforestry Systems, 2001)

Growth variability in a Senegalese provenance of Acacia nilotica ssp. tomentosa - E. Wolde-Mieskel; F. L. Sinclair (Agroforestry Systems, 2000)

Cod and haddock spawning on Georges Bank in relation to water residence times - F. H. Page; M. Sinclair; C. E. Naimie; J. W. Loder; R. J. Losier; P. L. Berrien; R. G. Lough (Fisheries Oceanography, 1999)
The seasonal and geographical patterns of spawning for Georges Bank cod ( Gadus morhua ) and haddock ( Melanogrammus aeglefinus ) are estimated using composite distributions of stage I eggs derived from the Marine Resources Monitoring, Assessment and Prediction (MARMAP) data set (1977–1987). The inferred mean spawning locations are compared with patterns in particle residence times derived from a three‐dimensional prognostic circulation model that estimates the tidal and seasonal mean circulation. The comparisons indicate that cod and haddock spawning occurs at times and locations characterized by model residence times in excess of 35 d. The results are discussed in the context of fish population regulation theory, particularly the member/vagrant hypothesis and the concept of abundance‐dependent vagrancy.

Incorporation of indigenous knowledge and perspectives in agroforestry development - D. H. Walker; F. L. Sinclair; B. Thapa (Agroforestry Systems, 1995)

Incorporation of indigenous knowledge and perspectives in agroforestry development - B. Thapa; F. L. Sinclair; D. H. Walker (Agroforestry Systems, 1995)